A dynamic polyurea network with exceptional creep resistance. Issue 39 (16th September 2022) - Ma, Yan; Wang, Hong-Qin; Zhao, Pei-Chen; Wang, Fang-Zhou; Li, Cheng-Hui
Abstract : We have designed and synthesized a new dynamic polyurea network with highly cross-linked inner "cores" and abundant flexible outer branches which shows superior creep resistance and reprocessibility. Abstract : Thermosetting polymers enjoy outstanding static performance at the expense of poor reprocessability and recyclability. The design of covalent adaptable networks (CANs) provides a possible solution, but most of them show poor solvent and creep resistance due to their dynamic nature. Herein, we designed and synthesized a new dynamic polyurea network with highly cross-linked inner "cores" and abundant flexible outer branches. The immobile inner "cores" can resist deformation during service and thus improve creep and chemical resistance, while the mobile outer branches can diffuse and rearrange at the interface to realize reprocessability. The new strategy offers new possibilities to seek a balance between material dynamic properties and static properties. Based on the dynamic and creep resistant polyurea network, a new adhesive with tough bonding strength as well as exceptional creep resistance and reprocessability was fabricated. Such high performance adhesive will be useful in automobile manufacture industry, construction industry, or even aerospace industry.